A new bathymetric compilation for the South Orkney Islands region, Antarctic Peninsula (49°–39°W to 64°–59°S): Insights into the glacial development of the continental shelf. (24th June 2014) - Dickens, William A.; Graham, Alastair G. C.; Smith, James A.; Dowdeswell, Julian A.; Larter, Robert D.; Hillenbrand, Claus‐Dieter; Trathan, Phil N.; Erik Arndt, Jan; Kuhn, Gerhard
Abstract We present a new, high resolution (300 m) bathymetric grid of the continental shelf surrounding the South Orkney Islands, northeast of the Antarctic Peninsula. The new grid, derived from a compilation of marine echo‐sounding data, improves previous regional bathymetric representations and helps to visualize the morphology of the shelf in unrivalled detail. The compilation forms important baseline information for a range of scientific applications and end users including oceanographers, glacial modelers, biologists, and geologists. In particular, due to the limited understanding of glacial history in this region, the bathymetry provides the first detailed insights into past glacial regimes. The continental shelf is dominated by seven glacially eroded troughs, marking the pathways of glacial outlets that once drained a former ice cap centered on the South Orkney Islands. During previous glacial periods, grounded ice extended to the shelf edge north of the islands. A large, ∼250 km long sediment depocenter, interpreted as a maximum former ice limit of one or more Cenozoic glaciations, suggests that ice was only grounded to the ∼300–350 m contour in the south. Hypsometric analyses support this interpretation, indicating that a significant proportion of the shelf has been unaffected by glacial erosion. Using these observations, we propose a preliminary ice cap reconstruction for maximum glaciation of the South Orkney plateau, suggesting an ice coverage of about ∼19, 000 km2. The timing of maximum ice extent, number of past advances and pattern of subsequent deglaciation(s) remain uncertain and will require further targeted marine geological and geophysical investigations to resolve.